The Impact of Ownership Concentration on the Cost of Equity Capital with Earnings Management as a Mediating Variable - Zunfani, Rita Mutiara; Hadiwibowo, Imam; Azis, Muhammad Taufik (Jurnal Penelitian Ekonomi dan Bisnis, 2025)
This study investigates the impact of ownership structure and earnings management on equity costs and explores whether earnings management mediates the relationship between ownership concentration and equity costs in technology companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Ownership structure is assessed based on the largest shareholders, while earnings management is measured through discretionary accruals using the Modified Jones Model. The sample comprises 13 companies with 65 observations, selected through purposive sampling and analyzed using multiple linear regression with EViews 8. The findings indicate that while ownership concentration can lower equity costs, it does not influence earnings management, and earnings management does not affect equity costs. Additionally, earnings management does not mediate the link between ownership concentration and equity costs, as major shareholders prioritize transparency in financial statements. Future research should consider different variables and include other sectors, such as mining and banking, to provide a more comprehensive and relevant understanding of equity costs across various industries and offer improved recommendations for companies and investors.